PENGARUH INTANGIBLE ASSET DAN LIKUIDITAS TERHADAP FINANCIAL DISTRESS (PADA PERUSAHAAN SEKTOR INDUSTRI YANG TERDAFTAR DI BEI TAHUN 2018-2020) - Roida Setyoningrum; Dwi Urip Wardoyo; Amila Solihan Amin; Raysita Sabilla (Jurnal Publikasi Ekonomi dan Akuntansi, 2022)
This study was aimed to examine the effect of intangible asset and liquidity on financial distress. The population of this study is industry sector companies listed in Indonesia Stock Exchange for the period 2018-2020. Purposive sampling as the sampling method was chosen, and so 28 companies were collected for the sample. The data used are secondary data and logistic regression was used as the method of data analysis using SPSS software version 26. The results showed that simultaneously and partially, intangible asset and liquidity have impact on financial distress.